METHODS FOR EVALUATING COGNITIVE SKILLS IN PRESCHOOLERS WITHIN THE MODERN INFORMATION ENVIRONMENT (Eureka Journal of Humanities and Social Research, 2026)
In the modern information environment saturated with digital technologies, preschoolers are exposed to intensive influence from screens and interactive devices, creating new challenges for their cognitive development. The problem lies in the fact that traditional methods of assessing cognitive skills, such as observation and paper-based tests, do not fully account for the impact of digital factors on attention, memory, executive functions, and social cognition, which can lead to underestimation or overestimation of a child's development. The aim of this article is to analyze existing methods for assessing cognitive skills in preschool children (3-6 years old) within the context of the digital environment, identify their advantages and limitations, and propose recommendations for integrating digital tools for more accurate diagnostics. The study found that combined approaches, including digital platforms (such as tablet-based tests and applications for assessing computational thinking), allow for an increase in measurement accuracy by 20-30% compared to traditional methods, accounting for individual factors such as screen time exposure and parental mediation. The achieved results emphasize the need to develop hybrid assessment protocols that integrate neurophysiological and behavioral data to optimize educational practices in the digital age.
Keywords: Cognitive skills, preschoolers, digital environment, assessment methods, executive functions.